PENGARUH ORGANIZATIONAL CULTURE, SERVANT LEADERSHIP, DAN NON- PHYSICAL WORK ENVIRONMENT TERHADAP MOTIVASI DAN JOB PERFORMANCE - Wiwoho, Gunarso (P4M STIE Putra Bangsa, 2016)
This study aims to examine and analyze the influence of organizational culture, servant leadership, and non-physical work environment on motivation and job performance in employees of the Central Bureau of Statistics of Kebumen Regency. Data collection is done by a questionnaire using a 4 Likert scale option. The population of this study is the total number of employees, namely 44 employees. Sampling techniques with saturated sampling techniques or all employees as research respondents. Data analysis techniques using descriptive analysis techniques and statistics include validity test, reliability test, classic assumption test, hypothesis test, correlation analysis, and path analysis (path analysis) with the help of SPSS for windows version 23.0. The results of this study namely organizational culture have no effect on motivation. Servant leadership has a positive and significant effect on motivation. The non-physical work environment has a positive and significant effect on motivation. Organizational culture has a positive and significant effect on job performance. Servant leadership does not affect job performance. Non-physical work environment does not affect job performance, and Motivation has a positive and significant effect on job performance.